Risk factors and outcome of epilepsy in adults with cerebral palsy or intellectual disability - Pérez, Isabel Fernández; Villagra, Tamara Biedermann; Jiménez-Balado, Joan; Redondo, Jordi Jiménez; Recasens, Bernat Bertran (Epilepsy & behavior, 2023)
Epilepsy is found in 10–60% of individuals with cerebral palsy (CP) and 5.5–35% with intellectual disability (ID). However, little is known about the long-term evolution of epilepsy among adults. The aim of the study is to describe the factors associated with epilepsy and its outcome in a population of adults with CP or ID. This retrospective study reviewed the medical records of 306 individuals with CP/ID. All individuals underwent neurological, psychiatric, and neuropsychological follow-ups. In the cohort, 72.5% of the individuals had a CP diagnosis, with a mean age of 36.4 years (IQR 24.0–46.0). Epilepsy was present in 55.6% of the individuals and was associated with CP (p < 0.01), spastic subtype (p < 0.01), a higher degree of ID (p < 0.01), hemorrhagic and congenital malformation etiologies (p 0.011), abnormal neuroimaging (p < 0.01), and worse scores on motor and communication scales (p < 0.01). Drug-resistant epilepsy (DRE) (22.4%) was associated with higher scores on motor scales (p < 0.01). Additionally, 42.3% of the individuals who attempted antiseizure medication (ASM) withdrawal experienced recurrence, which was associated with epileptic activity on the electroencephalogram (EEG) (p 0.004). Epilepsy is a common comorbidity in adults with CP or ID and is associated with greater brain damage and a more severe phenotype. Seizure recurrence after ASM withdrawal occurred in half of the individuals and was associated with epileptic activity on the EEG.